Amino acid profile characterization during the co-composting of a livestock manure and maize straw mixture. (1st January 2021) - Yao, Xiaofang; Zhou, Haibin; Meng, Haibo; Ding, Jingtao; Shen, Yujun; Cheng, Hongsheng; Zhang, Xi; Li, Ran; Fan, Shengyuan
Abstract: Amino acids (AAs) are important functional substances in compost product. The evolution of three groups of AAs was determined during the co-composting of pig manure and maize straw mixture. And the correlations between AAs and other humification indicators such as lignocellulose, phosphatase activity, and humic substances (HSs) were analyzed. Results showed that the total AA content decreased during the primary fermentation but increased to 3.578 g kg −1 after the second fermentation, exhibiting a 1.5-fold increase in the final compost. The neutral phosphatase activity, hemicellulose, and HSs had a promoting effect on AAs. Generally, the compost product quality was significantly improved due to the increment of AAs and additional small molecules during the secondary fermentation. Our study provided a new direction for future research on improving composting products of organic waste. Graphical abstract: Image 1 Highlights: The amino acids profile during manure-straw composting was studied. Amino acids are divided into growth-promoting, salt and heavy metal resistant types. Amino acids content exhibited a 1.5-fold increase in final compost. Amino acids are related to humus, hemicellulose and phosphatase activities. Compost products quality was improved due to the increment of amino acids.